2009
DOI: 10.1063/1.3184024
|View full text |Cite
|
Sign up to set email alerts
|

An infrared imaging method for high-throughput combinatorial investigation of hydrogenation-dehydrogenation and new phase formation of thin films

Abstract: Positron depth profiling of the structural and electronic structure transformations of hydrogenated Mg-based thin films J. Appl. Phys. 105, 043514 (2009) We have developed an infrared imaging setup enabling in situ infrared images to be acquired, and expanded on capabilities of an infrared imaging as a high-throughput screening technique, determination of a critical thickness of a Pd capping layer which significantly blocks infrared emission from below, enhancement of sensitivity to hydrogenation and dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…It was further demonstrated that this technique could be used to monitor metal to semiconductor, as well as metal to metal transformations; this finding is important since many hydrogen storage materials can exhibit multiple decomposition steps, and not all of the products are insulating. 313,320 CCS libraries of hydrogen storage materials enable measurement of the thermodynamic properties, but to determine reaction kinetics, it is useful to employ thickness wedge libraries, where the importance of grain size on the reaction rates can be studied. Materials such as MgH 2 strongly inhibit the diffusion of hydrogen, and thus present a substantial barrier to efficient hydrogenation.…”
Section: Thin Film Combinatorial Workmentioning
confidence: 99%
“…It was further demonstrated that this technique could be used to monitor metal to semiconductor, as well as metal to metal transformations; this finding is important since many hydrogen storage materials can exhibit multiple decomposition steps, and not all of the products are insulating. 313,320 CCS libraries of hydrogen storage materials enable measurement of the thermodynamic properties, but to determine reaction kinetics, it is useful to employ thickness wedge libraries, where the importance of grain size on the reaction rates can be studied. Materials such as MgH 2 strongly inhibit the diffusion of hydrogen, and thus present a substantial barrier to efficient hydrogenation.…”
Section: Thin Film Combinatorial Workmentioning
confidence: 99%
“…In recent years normalized infrared (IR) emissivity imaging has been revealed to be a potent characterization tool for studying hydrogen storage in thin films [1,2]. In this measurement technique IR images of a thin film and of a hydrogen-inert reference material are recorded with an IR camera simultaneously during hydrogenation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The NIRE system used here has been described in detail in a previous publication [12]. Briefly, the films were measured in a specially designed hydrogenation chamber fitted with a sapphire window.…”
Section: Methodsmentioning
confidence: 99%